INDEKS DESA MEMBANGUN (IDM) DI KABUPATEN BARITO KUALA - Novita Sari; Tomy Oktavianor (Universitas Lambung Mangkurat, 2020)
This study aims to describe the villages in Barito Kuala Regency based on the Building Village Index (IDM) and find out the direction of policies related to disadvantaged villages in Barito Kuala Regency. This study uses Mix Methodes approach, with the type of research being explanatory sequential. Based on data from the Build Village Index Recapitulation from the Barito Kuala Regency Community and Village Empowerment Office in 2017, it shows that the percentage of underdeveloped villages in Barito Kuala Regency reaches 64% or reaches 126 villages, so it must be a big concern for the local government. Determining the status of the village uses the Building Village Index by the Ministry of Village as a measure consisting of 3 aspects, namely the Social Resilience Index (IKS), the Economic Resilience Index (IKE) and the Environmental Resilience Index (IKL). In reducing the number of underdeveloped villages in Barito Kuala Regency, the government must pay attention to these three aspects to take a policy that can reduce the number of underdeveloped villages. The results showed that the Economic Resilience village was the index with the lowest value, followed by the Environmental Resilience Index and the Social Resilience Index. Based on this, the local government plan two policies, namely the first priority for village fund use which includes two things, namely increasing the economic activities of rural communities and improving the quality of life of rural communities, and the second through Integrated Village Surgery programs.